Contrasting Effects of a Nonionic Surfactant on the Biotransformation of Polycyclic Aromatic Hydrocarbons to cis-Dihydrodiols by Soil Bacteria - Allen, Christopher C. R. (American Society for Microbiology, 1999)
The biotransformation of the polycyclic aromatic hydrocarbons (PAHs) naphthalene and phenanthrene was investigated by using two dioxygenase-expressing bacteria, Pseudomonas sp. strain 9816/11 and Sphingomonas yanoikuyae B8/36, under conditions which facilitate mass-transfer limited substrate oxidation. Both of these strains are mutants that accumulate cis-dihydrodiol metabolites under the reaction conditions used. The effects of the nonpolar solvent 2,2,4,4,6,8,8-heptamethylnonane (HMN) and the nonionic surfactant Triton X-100 on the rate of accumulation of these metabolites were determined. HMN increased the rate of accumulation of metabolites for both microorganisms, with both substrates. The enhancement effect was most noticeable with phenanthrene, which has a lower aqueous solubility than naphthalene. Triton X-100 increased the rate of oxidation of the PAHs with strain 9816/11 with the effect being most noticeable when phenanthrene was used as a substrate. However, the surfactant inhibited the biotransformation of both naphthalene and phenanthrene with strain B8/36 under the same conditions. The observation that a nonionic surfactant could have such contrasting effects on PAH oxidation by different bacteria, which are known to be important for the degradation of these compounds in the environment, may explain why previous research on the application of the surfactants to PAH bioremediation has yielded inconclusive results. The surfactant inhibited growth of the wild-type strain S. yanoikuyae B1 on aromatic compounds but did not inhibit B8/36 dioxygenase enzyme activity in vitro.